Public Research, Local Knowledge Transfer, and Regional Development: Insights from a Structural VAR Model. (November 2020) - Eberle, Jonathan; Brenner, Thomas; Mitze, Timo
This article estimates the regional economic effects of public research activities. In order to identify the underlying transmission channels from knowledge creation to the regional environment, the empirical identification strategy goes beyond traditional partial effects analyses and studies the complex linkages between public research, innovativeness, and regional development on the basis of a structural vector autoregressive model. A particular focus is thereby set on assessing whether the effects of local public research activity differ by the type of research actors (universities, technical colleges, and public research institutes). The empirical results indicate that an increase in the volume of (public) third-party funding to technical colleges is associated with a rise in the regional investment and employment rate as well as the human capital stock. Increasing public third-party funding to both universities and technical colleges positively affects the regional patent activity, the employment rate, and per workforce output. In comparison, the empirical results provide limited evidence for regional economic effects stemming from an increase in local knowledge creation measured in terms of scientific publications. Here, only variations in the publication rate of public research institutes can be linked to positive private sector investment and employment effects.